2014
DOI: 10.4254/wjh.v6.i2.92
|View full text |Cite
|
Sign up to set email alerts
|

Association between inherited monogenic liver disorders and chronic hepatitis C

Abstract: AIM:To determine the frequencies of mutations that cause inherited monogenic liver disorders in patients with chronic hepatitis C. METHODS:This study included 86 patients with chronic hepatitis C (55 men, 31 women; mean age at diagnosis, 38.36 ± 14.52 years) who had undergone antiviral therapy comprising pegylated interferon and ribavirin. Viral load, biochemical parameter changes, and liver biopsy morphological data were evaluated in all patients. The control group comprised 271 unrelated individuals represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…After pretreatment analysis of liver function tests and biochemical markers commonly used for diagnostic orientation in patients with CHC, we found significant associations of the bilirubin and ferritin levels with UGT1A1 *28 genotype, similar to results by Piekuse L. et al (37) and de Souza et al (5). Hyper bilirubinemia caused by reduced UGT1A1 activity in patients with hepatitis C has been documented in reports of severe ribavirin-induced jaundice, after com mencing pegylated interferon and ribavirin therapy, suggesting usefulness of genotyping for UGT1A1 *28 variant for the decision to continue therapy with ribavirin (38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After pretreatment analysis of liver function tests and biochemical markers commonly used for diagnostic orientation in patients with CHC, we found significant associations of the bilirubin and ferritin levels with UGT1A1 *28 genotype, similar to results by Piekuse L. et al (37) and de Souza et al (5). Hyper bilirubinemia caused by reduced UGT1A1 activity in patients with hepatitis C has been documented in reports of severe ribavirin-induced jaundice, after com mencing pegylated interferon and ribavirin therapy, suggesting usefulness of genotyping for UGT1A1 *28 variant for the decision to continue therapy with ribavirin (38).…”
Section: Discussionsupporting
confidence: 89%
“…Bilirubin levels have also been observed to correlate with the total number of TA repeats (2, 5). The observed association of UGT1A1 *28 allele with serum ferritin levels has been previously documented in few studies which included patients with CHC (37). Serum iron markers (ferritin and transferrin) are suggested as surrogate markers for liver fibrosis and necroinflammatory activity.…”
Section: Discussionmentioning
confidence: 68%
“…A recent study on young patients under 10 years of age revealed that zinc monotherapy reduced serum ALT levels ranging from 243 ± 151 to 70 ± 29 IU/L in 1 month. 23 It is also important that copper-overload conditions secondary to chronic cholestasis 24 or chronic liver diseases other than WD 25,26 could be differentiated by the short-term treatment test.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate a gene-by-environment interaction between hepatitis C and AATD risk alleles. Previous studies have investigated whether there is an enrichment of individuals with AATD risk alleles within a population of patients with liver disease and have been inconclusive; some show no association between AATD risk alleles [21][22][23] and liver disease and others demonstrate an enrichment of these alleles in patients with hepatitis C related liver disease [18][19][20]24]. A recently published prospective study of individuals with chronic hepatitis C infection showed that there was no difference in the prevalence of Z allele heterozygotes in patients with cirrhosis compared with those without cirrhosis in two cohorts [49].…”
Section: Discussionmentioning
confidence: 99%
“…There are known environmental exposures that can exacerbate or accelerate tissue damage secondary to AATD in both heterozygotes and homozygotes including smoking, environmental pollution, respiratory infections, obesity, non-steroidal anti-inflammatory drugs, and alcohol [13][14][15][16][17]. There are additional environmental factors, like viral hepatitis, whose impact on exacerbating AATD-related tissue damage is debated [13,[18][19][20][21][22][23][24]. Early AATD diagnosis can lead to an avoidance of these environmental exposures and an attenuation of symptom manifestation [12,25].…”
Section: Introductionmentioning
confidence: 99%